Pengaruh Advertising dan Sales Promotion Terhadap Keputusan Menginap di Hotel POP! Diponegoro Surabaya - Lintang, Dyayu Lintang Kinanti (Universitas Negeri Surabaya, 2025)
This study aims to explore the influence of advertising and sales promotion on consumers’ decisions to stay at budget hotels in Surabaya. Specifically, it seeks to assess whether these two marketing variables significantly affect consumer behavior, both independently and jointly, in the hospitality industry. The research also intends to offer empirical evidence regarding the effectiveness of promotional activities implemented by budget hotels. By doing so, it strives to deliver strategic insights for developing more personalized and impactful marketing communications. With the increasing use of digital platforms and social media, understanding how these channels shape consumer perceptions and decisions becomes essential particularly in a competitive and price-sensitive market. From an academic perspective, the findings are expected to enrich the literature on service marketing by examining consumer responses to advertising and promotions within the context of affordable lodging options. Practically, the study serves as a tool for hotel managers to understand their target audience better and to design data-informed promotional strategies that align with the evolving needs and expectations of value-conscious travelers. This dual emphasis on theoretical contribution and practical application, the study to offer meaningful input for both marketing scholarship and managerial practice in Indonesia’s tourism landscape.